1988
DOI: 10.1111/j.1365-2125.1988.tb03408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haemodialysis on metoclopramide kinetics in patients with severe renal failure.

Abstract: The kinetics of metoclopramide and the effects of haemodialysis on metoclopramide kinetics were examined in eight uraemic subjects 1 h and 24 h prior to the onset of dialysis. In spite of the relatively minor contribution of renal clearance to total body clearance in normals, metoclopramide kinetics were substantially altered in uraemia. The total body clearance was decreased by 2-4 fold, terminal elimination half-life proportionately increased, while the volume of distribution appeared to be unaffected compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Normalizing renal function with a kidney transplant completely reversed the inhibitory effects of serum on liver P450 compared to predialysis serum (Figure 6). Although no studies have been performed on liver P450 and renal transplantation, some authors have reported an increase in the metabolic clearance of drugs after successful kidney transplantation compared to dialysis (Wright et al ., 1988; Kim et al ., 1993). For instance, the nonrenal clearance of isoniazid and metoclopramide markedly increase following kidney transplantation compared to the clearance observed in hemodialysis (Wright et al ., 1988; Kim et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Normalizing renal function with a kidney transplant completely reversed the inhibitory effects of serum on liver P450 compared to predialysis serum (Figure 6). Although no studies have been performed on liver P450 and renal transplantation, some authors have reported an increase in the metabolic clearance of drugs after successful kidney transplantation compared to dialysis (Wright et al ., 1988; Kim et al ., 1993). For instance, the nonrenal clearance of isoniazid and metoclopramide markedly increase following kidney transplantation compared to the clearance observed in hemodialysis (Wright et al ., 1988; Kim et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dopamine receptor antagonists may further impair striatal dopamine transmission and produce dopamine receptor hypersensitivity in the already-compromised basal ganglia of diabeticeuremic subjects. In addition, a significant proportion of the total body clearance of metoclopramide depends on adequate renal function, the half-life is markedly prolonged in chronic renal failure, 11 and the clearance of metoclopramide by CAPD is negligible because of its high molecular weight and large volume of distribution. 12 We speculated that metoclopramide therapy may further damage the vulnerable basal ganglia and lead to drug-induced parkinsonism and also the syndrome of acute bilateral basal ganglia lesions in this diabeticeuremic subject.…”
Section: Discussionmentioning
confidence: 99%
“…The CL of me to clop rami de in patients with renal impairment may be reduced by up to half (Bateman et al 1981;Wright et al 1988b); it is unaffected by haemodialysis, although anecdotal evidence suggests that the elimination rate returns to normal after transplantation (Wright et al 1988b). There are no published data on metoclopramide pharmacokinetics in liver disease, but I study suggested that very young children «1 month) may have impaired elimination of the drug (Kearns et al 1988).…”
Section: Metoclopramidementioning
confidence: 98%